SMOOTH MUSCLE TISSUE OF THE NIPPLE-AREOLA COMPLEX - Petrović, Aleksandar; Milentijević, Maja; Ilić, Ivan; Dencić, Tijana; Vidović, Nataša; Lazarević, Milica; Rančić, Ivan (Acta medicae Medianae, 2022)
The center of the breast integument is characterized by the roundish, glabrous (hairless) musculocutaneous specialization, nipple-areola complex, enriched with the integumentary class of smooth muscle tissue, which bundles are intimately intermingled with fibro-elastic connective tissue of the reticular dermis, with the openings of the distal, ending parts of excretory mammary gland ductal system, situated at the tip of the nipple. Inside this specific breast skin complex composed of two anatomically recognizable regions, muscle tissue is continuous, extending through the areola and nipple, nevertheless, functioning as one anatomic unit. Although present in both genders, in female physiology during the reproductive part of life, it is significantly more developed, and beside sexual arousal reaction, the major function of this structure is transitory contractile activity as essential part of physiological mechanisms necessary for regulated milk releasing during the period of breastfeeding. Nevertheless, analyzed in details and well defined from 19th century, latter, the topic of the nipple-areola complex muscular system in usual textbooks of anatomy and histology conceived unjustifiably a prejudice of marginality. Understanding the necessity for didactical recapitulation and systematization of data about the musculature of the complex and its associated structures, we reviewed the available literature, especially sources which were important for the theme and less often noticed in contemporary reviews.
Keywords: areola; nipple; smooth muscle tissue; Sappey; Meyerholtz